Design, analysis, and control of in-wheel switched reluctance motor for electric vehicles - Omac, Z.; Polat, M.; Oksuztepe, E.; Yildirim, M.; Yakut, O.; Eren, H.; Kurum, H. (Springer, 2018)
Estimation of dimension parameters for an electric machine has great importance before assembling on production line. As a matter of fact, researchers should find optimum solution once they decide to perform analytical design of an electric machine. In this study, we have tried to find dimensional and electrical parameters via derived mathematical equations for in-wheel switched reluctance motor (IW-SRM), and the motor has been manufactured. Moreover, an experimental setup is designed, and the speed and torque control of IW-SRM is carried out. The motor tests including both standstill and running test are performed by using the experimental setup. Initial size parameters are intuitively provided as motor analysis is conducted by software package. Then, numerous trials are examined to get optimum results. In fact, this motor is employed by an electric vehicle whose design is ongoing. Therefore, optimum motor parameters for required base speed and torque have been estimated by solving generated equations for IW-SRM with 18/12 poles via MATLAB. Considering parameters estimated, analysis of IW-SRM has been performed by Ansoft Maxwell 15.0 Software Package based on 3D finite element method (3D-FEM). Consequently, the estimated parameters have been validated by the results of Maxwell 3D FEM. Experimental results of the motor manufactured are obtained via the motor driver designed; also have been validated by Maxwell 3D.
Keywords: Designing in-wheel SRM; Electric vehicle; Optimum parameters estimation; Switched reluctance motor; Finite element method